Responsiveness of FGF-23 and mineral metabolism to altered dietary phosphate intake in chronic kidney disease (CKD): results of a randomized trial - Sigrist, Mhairi; Tang, Mila; Beaulieu, Monica; Espino-Hernandez, Gabriella; Er, Lee; Djurdjev, Ognjenka; Levin, Adeera (Nephrology, dialysis, transplantation, 2013)
High fibroblast growth factor-23 (FGF-23) levels are associated with adverse outcomes. We studied the responsiveness of FGF-23 and mineral metabolism to altered dietary phosphate intake in chronic kidney disease (CKD) and healthy control patients. Thirty patients were enrolled: 18 normophosphatemic CKD subjects and 12 healthy controls. The study duration was 21 days with three 7-day dietary interventions; a high phosphate (HP, 2000 mg/day), low phosphate (750 mg/day) and low phosphate plus phosphate binder (aluminum hydroxide, 500 mg thrice daily with meals), with comparable macronutrient content, administered in random sequence. Baseline and weekly fasting morning measurements of FGF-23, serum phosphate (sPO(4)), 1,25-hydroxyvitamin D (1,25 D) and 24-h urinary calcium (uCa) and phosphate (uPO(4)) were collected. FGF-23 levels were higher in subjects versus controls (72 pg/mL versus 30 pg/mL) at baseline, while sPO(4) remained in the normal range throughout the study. The absolute changes of uPO(4) and uCa for CKD and controls vary according to diet. The absolute changes of FGF-23 and sPO(4) suggest that the effect of the diets might also depend on the CKD status (P-values interaction effect = 0.08 and 0.07, respectively); nonetheless, these changes are evident as a function of dietary interventions, irrespective of CKD status (P-values diet effect = 0.006 and <0.001, respectively). FGF-23 levels appear to be responsive to changes in diet in both CKD patients and controls. Further studies are required to determine whether lowering dietary phosphate and thus FGF-23 levels are of long-term benefit in CKD patients, irrespective of sPO(4) levels.